PERSPECTIVES ON NUSYUZ AS A BASIS FOR DIVORCE FROM JUDGES OF THE JEMBER RELIGIOUS COURT - Farij Hamy Rosyid, Beni Ashari, (Mabahits : Jurnal Hukum Keluarga Islam, 2023)
The aim of this article is to examine the Jember Religious Court judges' perspectives on nusyuz as a basis for divorce. The study utilises a normative and legal approach through fieldwork research. The pivotal information source for this research is the Jember Religious Court judges. It should be noted that the judges' decision-making process is significantly influenced by the husband's consent to provide financial support during the iddah period. In conclusion, this research aligns with the husband's agreement to provide iddah maintenance to his spouse. Sometimes husbands neglect their obligations, which may lead to their wives committing nusyuz. The panel of judges has ruled that the wife is still entitled to iddah maintenance unless the nusyuz is related to bad faith and actions such as drunkenness, gambling, and adultery. b. The factors contributing to nusyuz by a wife include economic factors, infidelity, idleness, lack of interaction, and unrealistic expectations. The effect of nusyuz, which can lead to divorce, ultimately harms the family and causes a loss of harmony. The effect of nusyuz, which can lead to divorce, ultimately harms the family and causes a loss of harmony. The effect of nusyuz, which can lead to divorce, ultimately harms the family and causes a loss of harmony. Furthermore, children may be negatively impacted by their parents' divorce due to nusyuz, suffering from psychological disorders and trauma. The phenomenon of nusyuz has significant sociological impacts and is capable of disrupting familial relationships. It can lead to conflicts between spouses, extended family, and relatives.